ANTIBACTERIAL POTENTIAL OF KAPUL FRUIT SKIN (Baccaurea macrocarpa) ON Streptococcus sanguis - Norhayati Norhayati; Siti Ujrumiah; Annisa Noviany; Amy Nindia Carabelly (Odonto : Dental Journal, 2019)
Introduction: Recurrent aphthous stomatitis (SAR) is a recurrent ulceration lesion where many Streptococcus sanguis bacteria are found. Streptococcus sanguis bacteria can be killed by compounds that contain antibacterial. Kapul fruit (Baccaurea macrocarpa) is a typical Kalimantan fruit, has antioxidant and antibacterial activity which serves to kill Streptococcus sanguis. Method: Performed a quantitative phytochemical test on the kapul fruit peel and continued with the antibacterial activity test using the disc diffusion method of kapul fruit peel extract at the concentrations 20%, 40%, 60%, 80%, 100%,Chlorhexidine as a positive control and aquades as a negative (n=4/group). Result: From the phytochemical test, Kapul fruit peel extracts contain 35,851% of alkaloid, 23,225% of saponin, 2,395mg of tannin and 21,000mg of flavonoids. Kapul fruit peel extracts has the potential as an antibacterial against Streptococcus sanguis at concentration of 40%, 60%, 80% and 100%. The concentration at 100% has an equivalent to chlorhexidine as an antibacterial potential.Conclusion: The potential of Kapul peel Extract as antibacterial to Streptococcus sanguis bacteria on 40%, 60%, 80%, 100% concentration. The concentration at 100% has an equivalent to chlorhexidine as an antibacterial potential.